DEVELOPER'S LEGAL RESPONSIBILITY FOR FAILURE TO BUILD A HOUSE AND ITS CORRELATION WITH THE GOOD FAITH PRINCIPLE - Agustina (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to comprehensively examine the importance of good faith in every agreement and to discuss in depth the form of developer's legal liability for failed buildings. This type of research is normative in nature with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on statutory regulations and legal norms. The results of this study indicate that any agreement must be made based on honesty and good faith to ensure equal rights or proportionality of the parties who are bound to the agreement. The forms of developer's legal liability for failed buildings are divided into three, namely administrative liability (written warnings, administrative fines, temporary suspension of service activities, blacklisting and freezing or revocation of permits), civil (material and immaterial damages) and criminal liability. (imprisonment and fines). The conclusions in this study are: standard clauses that are waiver or transfer of responsibility as well as those that violate consumer rights by the developer in the agreement are contrary to the terms of the validity of the agreement as stipulated in Articles 1320 and 1338 paragraph (3) of the Civil Code (every agreement must be based on good intention). For agreements that are deliberately made in bad faith to harm one of the parties, based on the Jurisprudence of the Supreme Court of the Republic of Indonesia Number: 4/Yur/Pid.B/2018, in conjunction with the Jurisprudence of the Supreme Court of the Republic of Indonesia Number: 366 K/Pid.2016, is included in fraud crime.